Studies in the History of Tax Law, Volume 6 (Hart Publishers, 2013)
These are the papers from the 2012 Cambridge Tax Law History Conference revised and reviewed for publication. The papers include new studies of: income tax law rewrite projects 1914-1956; law and administration in capital allowances 1878- 1950; the 'full amount' in income tax legislation; Sir Josiah Stamp and double income tax; early German income tax treaties and laws concerned with double tax avoidance (1869-1908); the policy of the medicine stamp duty; 'Danegeld' - from Danish tribute to English land tax; religion and charity, a historical perspective; 'Plaintive Glitterati'; a collision of accounting and law, dividends from pre-1914 profits in Australia; the history and development of the taxation profession in the UK and Australia; an inquiry into Dutch to British Colonial Malacca 1824-1839; the taxation history of China; taxing bachelors in America: 1895-1939; Dutch Tax reform under Napoleon; and the last decade of estate duty.
English
Keywords: Legal history; Taxation & duties law; history of law; income tax law; tax law